Prevalence, Perceptions and Profile of Gastroesophageal Reflux Disease in A Rural Population of North Bihar - Kumar, Sanjeev; Shivalli, Sidharuda (National Journal of Community Medicine, 2014)
Background: The prevalence of gastro esophageal reflux disease (GERD) in India ranges from 8-20% according to recently conducted studies based on different case definitions and study methodology. Reports of its association with risk factors are inconsistent between studies. There are lack population based studies to know about the epidemiology of this disease. This study was therefore done to assess the prevalence, symptom profile and perceived precipitating factors of GERD in a rural population of northern Bihar. Methodology: A community based descriptive cross sectional study was undertaken from April 2013 to July 2013 on 2000 adults (above 20 years) from 20 clusters of 5 adjoining villages of Madhubani district in north Bihar. Clusters were selected from the different pockets (mohallas) of the villages. A semi-structured questionnaire translated into local language was used to collect data regarding symptoms, lifestyle, precipitating factors and socio-demographic characteristics of those affected with GERD. Results: The prevalence of GERD in this population was 23.6%.The prevalence among males and females was 18% and 30% respectively. Prevalence was more among Muslims than Hindus. Heartburn accompanied by regurgitation was the predominant symptom. Low socioeconomic status, female gender, age group of 31-40 years was associated with this condition. Large fatty and spicy diet, postprandial posture, consumption of meat, tea and Malda variety of mangoes were perceived as precipitating/aggravating factors by the cases. Conclusion: There is high prevalence of GERD in this population. Analytical studies are recommended to test its association with the observed factors.